Is the Invasive Species Listronotus bonariensis (Kuschel) (Coleoptera: Curculionidae) (Argentine Stem Weevil) a Threat to New Zealand Natural Grassland Ecosystems? - Barratt, Barbara I. P.; Barton, Diane M.; Philip, Bruce A.; Ferguson, Colin M.; Goldson, Stephen L. (Frontiers in Plant Science, 2016)
Listronotus bonariensis (Argentine stem weevil) is a stem-boring weevil that has become a major pasture pest in New Zealand, and cool climate turf grass in Australia. This species is also frequently found in native tussock grassland in New Zealand. Laboratory and field trials were established to determine the risk posed to both seedlings and established plants of three native grass species compared to what happens with a common host of this species, hybrid ryegrass (L. perenne X L. multiflorum). Adult weevil feeding damage scores were higher on Poa colensoi and Festuca novae-zelandiae than Chionochloa rigida. Oviposition was lower on P. colensoi than hybrid ryegrass, and no eggs were laid on F. novae-zelandiae. In field trials using the same four species established as spaced plants L. bonariensis laid more eggs per tiller in ryegrass in a low altitude pasture site than in ryegrass in a higher altitude site. No eggs were found on the three native grass species at the tussock sites, and only low numbers were found on other grasses at the low altitude pasture site. Despite this, numbers of adult weevils were extracted from the plants in the field trials. These may have comprised survivors of the original weevils added to the plants, together with new generation weevils that had emerged during the experiment. Irrespective, higher numbers were recovered from the tussock site plants than from those from the pasture site. It was concluded that L. bonariensis is likely to have little overall impact, but a greater impact on native grass seedling survival than on established plants.